Post-COVID-19 Depressive Symptoms: Epidemiology, Pathophysiology, and Pharmacological Treatment - Mazza, Mario Gennaro; Palladini, Mariagrazia; Poletti, Sara; Benedetti, Francesco (CNS drugs, 2022)
The Coronavirus Disease 2019 (COVID-19) pandemic is still spreading worldwide over 2 years since its outbreak. The psychopathological implications in COVID-19 survivors such as depression, anxiety, and cognitive impairments are now recognized as primary symptoms of the “post-acute COVID-19 syndrome.” Depressive psychopathology was reported in around 35% of patients at short, medium, and long-term follow-up after the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) infection. Post-COVID-19 depressive symptoms are known to increase fatigue and affect neurocognitive functioning, sleep, quality of life, and global functioning in COVID-19 survivors. The psychopathological mechanisms underlying post-COVID-19 depressive symptoms are mainly related to the inflammation triggered by the peripheral immune-inflammatory response to the viral infection and to the persistent psychological burden during and after infection. The large number of SARS-CoV-2-infected patients and the high prevalence of post-COVID-19 depressive symptoms may significantly increase the pool of people suffering from depressive disorders. Therefore, it is essential to screen, diagnose, treat, and monitor COVID-19 survivors’ psychopathology to counteract the depression disease burden and related years of life lived with disability. This paper reviews the current literature in order to synthesize the available evidence regarding epidemiology, clinical features, neurobiological underpinning, and pharmacological treatment of post-COVID-19 depressive symptoms.